How perceived control drives approach job crafting through a psychological authentic climate and perceived insider status - Li, Lin; Chen, Chun-Shuo (Edelweiss Applied Science and Technology, 2025)
This study investigates the mechanisms through which perceived control influences approach job crafting and the key factors involved. It also deepens understanding of the internal logic of the approach job crafting. Drawing on self-determination theory, a research model was developed that posits psychological authentic climate and perceived insider status serve as mediators, with informal leadership emergence functioning as a moderator. This study collected 532 valid samples from employed individuals in Beijing, Shanghai, Guangzhou, and Shenzhen using purposive sampling. Results indicate that psychological authentic climate and perceived insider status partially mediate the relationships under examination. Additionally, the emergence of informal leadership positively moderates the relationships linking perceived control and perceived insider status to approach job crafting. This study extends the theoretical framework connecting perceived control with approach job crafting and offers practical guidance for organizations seeking to stimulate employee proactivity by fostering a psychological authentic climate and a supportive environment.